Comparison of anomalies in the VLF spectrum of the natural electromagnetic field with data from the seismometer in a landslide-affected area - HOFFMAN, Michal; KOČI, Eduard (Contributions to Geophysics and Geodesy, 2024)
The data from a permanent monitoring station, based on a sound card as an AD/DA converter and a magnetic loop antenna for continuous recording of electromagnetic field intensities in the Very Low Frequency (VLF) range, were recorded and compared with data from a seismic station based on Raspberry Pi located in a landslide-affected area. The stations operated 24/7 and were placed in a room below ground level. Correlations were observed between seismic signals in the frequency spectrum from 0.1 Hz to 10 Hz (some extending beyond 20 Hz) and anomalies in the electromagnetic field in the VLF range. These anomalies are likely associated with micro-fracturing, piezo-electromagnetic, and triboelectric phenomena within the landslide body, producing relatively weak VLF emissions and a faint seismic signal. A single-component 4.5 Hz 395 Ohm vertical Racotech RGI-20DX geophone with electronic extension to lower frequencies (< 1 Hz) was used with a sampling rate of 100 sps (samples per second). VLF emissions cover almost the entire spectrum from 6 kHz with a peak at 14 kHz to 18 kHz. The received spectrum was divided into following sections: VLF band 4 kHz – 6 kHz; 6 kHz – 8 kHz; 8 kHz – 10 kHz; 10 kHz – 12 kHz; 12 kHz – 14 kHz; 14 kHz – 16 kHz; 16 kHz – 18 kHz. Simultaneously, there were changes in these sections analysed and compared with the seismic record within the same time interval.